Ghanaian academic libraries’ use of social media: A structural equation modelling approach - Mensah, M.; Onyancha, O.B. (SAGE, 2021)
The study was largely quantitative and employed the unified theory of acceptance and use of technology (UTAUT) as its theoretical lens. The target population was 31,157 consisting of library staff and library patrons from four academic libraries in Ghana. Sampling tables and census sampling techniques were used to select a sample size of 767 respondents. Adopting a cross-sectional survey design, the study used a pre-tested questionnaire to collect data from the sampled respondents. Statistical analyses were carried out using the Statistical Package for Social Sciences. The structural equation modelling technique was further used to estimate the relationships and correlations between the theoretical constructs from the UTAUT to understand behavioural intentions and use behaviour of social media in the academic libraries. The study found that performance expectancy, effort expectancy and facilitating conditions have significant influence on the intention to use and subsequent use of social media in academic libraries in Ghana.
Research Article
Keywords: social media; UTAUT; Structural equation modelling; academic libraries; Ghana